2012
DOI: 10.1111/j.1523-1739.2012.01926.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Macroalgal Expansion and Marine Protected Areas on Coral Recovery Following a Climatic Disturbance

Abstract: Disturbance plays an important role in structuring marine ecosystems, and there is a need to understand how conservation practices, such as the designation of Marine Protected Areas (MPAs), facilitate postdisturbance recovery. We evaluated the association of MPAs, herbivorous fish biomass, substrate type, postdisturbance coral cover, and change in macroalgal cover with coral recovery on the fringing reefs of the inner Seychelle islands, where coral mortality after a 1998 bleaching event was extensive. We visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 66 publications
2
65
3
Order By: Relevance
“…Taxonomic composition is often considered as the best descriptor of the overall status of ecosystems ; however, the high biodiversity of Maldivian coral reefs (Andr efou€ et, 2012) led us to adopt non-taxonomic descriptors that assemble species according to their ecological role (Darling et al, 2012;Wilson et al, 2012). In particular, we estimated the percent cover of five broad benthic categories (Lasagna et al, 2008): 1) hard (zooxanthellate) corals; 2) soft (zooxanthellate) corals; 3) other (azooxanthellate, suspension-feeding) invertebrates; 4) macroalgae; 5) abiotic attributes (sand, rock, coral rubble).…”
Section: Field Activitiesmentioning
confidence: 99%
“…Taxonomic composition is often considered as the best descriptor of the overall status of ecosystems ; however, the high biodiversity of Maldivian coral reefs (Andr efou€ et, 2012) led us to adopt non-taxonomic descriptors that assemble species according to their ecological role (Darling et al, 2012;Wilson et al, 2012). In particular, we estimated the percent cover of five broad benthic categories (Lasagna et al, 2008): 1) hard (zooxanthellate) corals; 2) soft (zooxanthellate) corals; 3) other (azooxanthellate, suspension-feeding) invertebrates; 4) macroalgae; 5) abiotic attributes (sand, rock, coral rubble).…”
Section: Field Activitiesmentioning
confidence: 99%
“…The one weak association was a negative association between acan thurids and coral cover that would indicate their preference for feeding on dead coral surfaces (Marshell & Mumby 2012). While this does not support some ecosystem management recommendations, it does correspond with a number of large-scale studies that have failed to find significant coral− parrot fish associations, identified other factors, or found that herbivorous fish passively associate with, rather than actively control, algae-coral relationships (McClanahan et al 2011b, Wilson et al 2012, Carassou et al 2013, Russ et al 2015, Suchley et al 2016.…”
Section: Discussionmentioning
confidence: 87%
“…While the stressors affecting coral populations can differ widely at the local level, competition with macroalgae and algal turfs has been recognized as a global cause of coral mortality (McCook et al 2001, Diaz-Pulido & McCook 2004, Birrell et al 2008, DiazPulido et al 2009, Barott et al 2012) and as a determinant of coral recovery from climatic disturbances (Wilson et al 2012). In fact, recent studies on the effectiveness of Marine Protected Areas have identified the preservation of an intact and diverse herbivore guild as one of the keys to enhancing coral resilience (Hughes et al 2007, Mumby et al 2007, Mumby & Steneck 2008.…”
Section: Abstract: Sea Urchin · Coral Production · Lytechinus · Algamentioning
confidence: 99%